Comparison Analysis of User Experience on m-BCA and BRImo Mobile Banking Applications Using The User Experience Questionnaire (UEQ) Method - Farhany Richas; Irsyad Kamal (CV Putra Publisher, 2024)
The increasing trend of non-cash payments such as QRIS and transfers is driving more intensive use of mobile banking applications in daily life. This poses a challenge for mobile banking service providers to deliver the best service to their customers through a good user experience. This is necessary to maintain their existence in the hearts of their customers. This research aims to determine the user experience value in each m-BCA and BRImo application, as well as their comparative value using the User Experience Questionnaire (UEQ) method. The analysis results conducted on 240 respondents with a minimum age of 19 and domiciled in Jabodetabek show that the user experience of BRImo is superior to m-BCA in all UEQ scales. BRImo achieves excellent benchmark scores in the attractive, perspicuity, efficiency, dependability, and stimulation scales while obtaining a good evaluation in the novelty scale. Meanwhile, m-BCA obtains excellent benchmark scores in the perspicuity, efficiency, and dependability scales, good evaluation on the attractive scale, above average on the stimulation scale, and below average on the novelty scale.